Efficacy of Warm Ginger Water Foot Soak Therapy on Hemodynamic Parameters and Chronic Pain in an Elderly Patient with Hypertension: A Case Study - Windhy Dwi Surya Arizana; Fahruddin Kurdi; Latifa Aini Susumaningrum (Jurnal Kegawatdaruratan Medis Indonesia, 2026)
Background: Hypertension remains a prevalent cardiovascular condition among the elderly, often accompanied by chronic pain and suboptimal medication adherence. Non-pharmacological interventions, such as relaxation therapy, serve as essential adjuncts to standard pharmacological management. Objective: This study aimed to analyze the efficacy of warm ginger water foot soak relaxation therapy on hemodynamic parameters and chronic pain in an elderly patient with hypertension. Methods: A single-case study design was employed involving a 78-year-old female with Grade 2 hypertension and chronic occipital headache. The participant exhibited baseline blood pressure of 170/90 mmHg and a Numeric Rating Scale (NRS) pain score of 5. The intervention consisted of warm ginger water foot soak therapy combined with deep breathing exercises, administered for 15–30 minutes twice daily over six sessions within two weeks. Outcome measures included systolic and diastolic blood pressure, pulse rate, and NRS pain scale assessed before and after each session. Results: Following six therapy sessions, the patient demonstrated a reduction in blood pressure from 170/90 mmHg to 140/80 mmHg and a decrease in pain intensity from NRS 5 to 1. The patient reported subjective improvement in headache symptoms and enhanced relaxation. Conclusion: Warm ginger water foot soak therapy combined with deep breathing relaxation is an effective, safe, and affordable non-pharmacological nursing intervention for reducing blood pressure and alleviating chronic pain in elderly patients with hypertension. This therapy can be integrated into comprehensive geriatric nursing care.